EFEKTIVITAS PROGRAM MADIN PASCA KBM DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN SISWA MTs SUMBERSARI KOWANG - Moh. Ainul Fawaid; Ilham Tri Wahyudhi; Ana Achoita (CV. ADIBA AISHA AMIRA, 2025)
This study aims to determine the effectiveness of the Madrasah Diniyah (Madin) program implemented after teaching and learning activities (KBM) in improving students' religious understanding at MTs Sumbersari Kowang. The Madin program after KBM is a school effort to strengthen students' religiosity through additional learning activities that focus on deepening faith, worship, morals, and reading and writing the Qur'an. The research method used is a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results show that the implementation of the Madin program is quite effective. This effectiveness is seen from the increasing ability of students to understand the basics of Islamic teachings and changes in more positive religious behavior in everyday life. Supporting factors for the program's success include support from Islamic Religious Education teachers, active student participation, and a religious school environment. The obstacles faced include limited time and varying levels of student understanding. Overall, the Madin program after KBM plays an important role in shaping character and deepening students' religious understanding at MTs Sumbersari Kowang.